2005
DOI: 10.1128/jb.187.19.6701-6707.2005
|View full text |Cite
|
Sign up to set email alerts
|

TolC Is Involved in Enterobactin Efflux across the Outer Membrane of Escherichia coli

Abstract: Escherichia coli excretes the catecholate siderophore enterobactin in response to iron deprivation. While the mechanisms underlying enterobactin biosynthesis and ferric enterobactin uptake and utilization are widely understood, nearly nothing is known about how enterobactin is exported from the cell. Mutant and highperformance liquid chromatography analyses demonstrated that the outer membrane channel tunnel protein TolC but none of the respective seven resistance nodulation cell division (RND) proteins CusA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
128
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(134 citation statements)
references
References 42 publications
6
128
0
Order By: Relevance
“…As a third alternative, a TolC-dependent but EntS-independent export system(s) that transports enterobactin from both the cytoplasm and the periplasm to the environment might exist. Enterobactin breakdown products, however, were also released through the OM in a tolC mutant (23), suggesting that there are further OM gates for clearing the periplasm from catecholate fragments.…”
Section: General Steps Of Siderophore Pathwaysmentioning
confidence: 96%
See 1 more Smart Citation
“…As a third alternative, a TolC-dependent but EntS-independent export system(s) that transports enterobactin from both the cytoplasm and the periplasm to the environment might exist. Enterobactin breakdown products, however, were also released through the OM in a tolC mutant (23), suggesting that there are further OM gates for clearing the periplasm from catecholate fragments.…”
Section: General Steps Of Siderophore Pathwaysmentioning
confidence: 96%
“…An E. coli fur tonB double mutant, which is derepressed in enterobactin synthesis but unable to take up Fe-enterobactin, reached only one-third of the dry weight of an enterobactin-deficient fur entC double mutant (23). Another study reported normal growth rates for an E. coli entB mutant and fes entB double mutant, both defective in enterobactin biosynthesis, but very poor growth of fes and fep mutants defective in Fe-enterobactin uptake and hydrolysis, respectively, under the same iron-depleted conditions (327).…”
Section: Conclusion and Future Conceptsmentioning
confidence: 99%
“…We observed uptake of ethidium (394 Da) and erythromycin (734 Da; Figs. [3][4][5][6][7][8][9][10][11], and a permeability coefficient for Anabaena sp. (Fig.…”
Section: An Anaomp85-independent Insertion Of Hgdd Into the Outermentioning
confidence: 99%
“…The final assembly of DHB and serine into enterobactin depends on the action of EntD, EntB, EntE, and EntF (11). Once enterobactin has been synthesized, it is transported through the inner membrane by EntS (12) and the outer membrane by TolC (13). Outside the cell, enterobactin will bind to ferric Fe (Fe 3+ ) with an extremely high affinity (14).…”
mentioning
confidence: 99%